KARAKTERISTIK FISIKOKIMIA DAN SENSORI VLA LABU PARANG (CUCURBITA MOSCHATA DURCH) - Mardiah, Mardiah (Universitas Djuanda, 2021)
This study aims to utilize Cucurbita Moschata D in processed products in the form of custard. There are threeresearch stages; the first stage is making pumpkin puree, the second stage is determining the concentration ofpumpkin puree and cornstarch to get the best custard texture. Then, Compare the concentration of granulatedsugar (25%, 27.5%, 30%, 32.5%, 35%) with two replications on the shelf life of custard, the third stage. Theresearch used a completely randomized design with one treatment factor comparing pumpkin puree withcornstarch with two repetitions. Product analysis includes organoleptic tests (sensory and hedonic tests),physical and chemical, and proximate tests. The first stage results showed that the ratio of pumpkin andcornstarch (16.6%: 5%) produced the best texture. This formula's chemical and physical tests were watercontent 7.81%, ash 0.084%, fat 7.53%, protein 9.02%, antioxidant activity 649,594 ppm, and beta carotene175.53 g/g. The results of the test of water content, pH, and TPC showed the best treatment at theconcentration of granulated sugar (32.5%) with storage time on the 1st, 3rd, 6th, and 9th days.